Charge Transport At Liquid/Liquid Interface - Al-Agealy, Hadi J. M.; Al-Saadi, Adil A. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Charge transfer (CT) at liquid/liquid interfaces are described theoretically depending on the quantum theory .A model that derived used to calculate the rate constant of transport at liquid/liquid interfaces. The calculation of the rate constant of charge transfer depends on the calculation of the reorganization energy, driving force ,and the coupling coefficient . Large reorganization energies and large rate constant for charge transfer ,indicate that the transitions involve more energy to happen . The system have large ð¸0 (ð‘’ð‘‰) refers that type of liquid is more reactive media than other liquid types with same donor. Driving force energy to drive the charge increases with the increase of absorption energy and decrease of in wave length. Height barrier at liquid/liquid interface that decreasing with decreasing the driving force energy and increasing the absorption energies .Charge transfer is so much small as a barrier of large values but in the low values of barrier ,the transfer is most probable. The large height barrier exclusion transfers across liquid/liquid system and the charger suffers from much resistant to transfer . However, this excluded transfer could be significantly large for high barrier and small concentrations .The theoretical values of rate constant of charge transfer show a good agreement with some of the experimental studies